Protective effect of carbon dots derived from scrambled Coptidis Rhizoma against ulcerative colitis in mice - Mou, Yanfang; Bai, Xue; Ma, Huagen; Li, Tingjie; Zhao, Yafang; Wu, Tong; Zhang, Yue; Qu, Huihua; Kong, Hui; Wang, Xueqian; Zhao, Yan (Frontiers in Molecular Biosciences, 2023)
Introduction: Ulcerative colitis (UC) is a chronic and progressive inflammatory disease of the intestines. The primary symptoms, such as bloody diarrhea, can result in weight loss and significantly diminish the patient’s quality of life. Despite considerable research endeavors, this disease remains incurable. The scrambled Coptidis Rhizoma (SCR) has a rich historical background in traditional Chinese medicine as a remedy for UC. Drawing from a wealth of substantial clinical practices, this study is focused on investigating the protective effects and underlying mechanisms of the active component of SCR, namely SCR-based carbon dots (SCR-CDs), in the treatment of UC. Methods: SCR-CDs were extracted and isolated from the decoction of SCR, followed by a comprehensive characterization of their morphological structure and functional groups. Subsequently, we investigated the effects of SCR-CDs on parameters such as colonic length, disease activity index, and histopathological architecture using the dextran sulfate sodium (DSS)-induced colitis mice model. Furthermore, we delved into the assessment of key aspects, including the expression of intestinal tight junction (TJ) proteins, inflammatory cytokines, oxidative stress markers, and gut microbial composition, to unravel the intricate mechanisms underpinning their therapeutic effects. Results: SCR-CDs displayed a consistent spherical morphology, featuring uniform dispersion and diameters ranging from 1.2 to 2.8 nm. These SCR-CDs also exhibited a diverse array of surface chemical functional groups. Importantly, the administration of SCR-CDs, particularly at higher dosage levels, exerted a noteworthy preventive influence on colonic shortening, elevation of the disease activity index and colonic tissue impairment caused by DSS. These observed effects may be closely associated with the hygroscopic capability and hemostatic bioactivity inherent to SCR-CDs. Concurrently, the application of SCR-CDs manifested an augmenting impact on the expression of intestinal TJ proteins, concomitantly leading to a significant reduction in inflammatory cell infiltration and amelioration of oxidative stress. Additionally, SCR-CDs treatment facilitated the restoration of perturbed gut microbial composition, potentially serving as a fundamental mechanism underlying their observed protective effects. Conclusion: This study demonstrates the significant therapeutic potential of SCR-CDs in UC and provides elucidation on some of their mechanisms. Furthermore, these findings hold paramount importance in guiding innovative drug discovery for anti-UC agents.